PLAUSIBILITY OF FICTIONAL AI COGNITIONS IN ISAAC ASIMOV’S I, ROBOT - Patrick, Callaghan Gerard; Selvam, Karuppasamy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Artificial Intelligence has become a vital area to explore in literature as significant importance has been given to the development of technologies, particularly computational technologies and robotics. In contemporary reality, it has become important to understand the standards in which Artificial Intelligence operates and functions in various disciplines that make life more efficient and convenient for human beings. Hence, it is essential to understand the limitations of its functions and operations. Science Fiction is an important genre in English Literature that explores possibilities for Artificial Intelligence development through sub-genres like Robotic Dystopias or Utopias, where realities about uncertain futures are assumed and visualized through the author’s imagery and the reader's interpretation. The title “Plausibility of Fictional AI Cognitions in Isaac Asimov’s I, Robot” is the study of the literary work of art by Isaac Asimov to highlight the interpretation made by the author about a 21st century reality in which almost all areas have robots programmed to perform various tasks. In a reality which is reliant on robots, it is extremely important to understand the ethics that govern them. The robots in the fix-up novel seem to be governed by the fictional: “Three Laws of Robotics”. Artificial Intelligence plays a role in the development of every robot’s positronic brain. In the series of stories that Isaac Asimov takes the reader through his work; a greater meaning in the metallic creatures is discovered, that the robots are capable of cognitive function that is hard to differentiate between living human beings. This brings an awareness that there is a plausibility in applying the same ethics pragmatically by understanding the ontological significance of the robot characters in the novel. This will provide scope for areas in philosophy, ethics, ontology and AI cognitive studies that are interdisciplinary and not limited to the field of literature.